Perkembangan Manajemen Strategi - Son Wandrial (The Winners, 2004)
Strategic management is an inter-discipline field which develops rapidly these days.Its development follows the other study disciplines like marketing, micro, macro, organization behaviour, etc. Strategic management development is also follows the changes in business environment, like industrial competition, consumer behaviour, and technology. Companies must adapt those changes if they still want to survive in business. If not, they will be lost. In order to survive, experts had announced many concept. And this article will briefly explain about the main concept which contributes in strategic management development.